Potential invasiveness by non-indigenous macrozoobenthos in the secondary hydrographic system of a temperate-climate river catchment. (May 2018) - Paganelli, Daniele; Pandolfi, Alessandra; Sconfietti, Renato; Marchini, Agnese; Vilizzi, Lorenzo
Highlights: NIS assemblage of a temperate-climate catchment. Level of biocontamination. Evaluation of NIS that may cause ecological/economic impacts in the study area. A first step towards the successful management of this aquatic system. Abstract: In the context of biological invasions, freshwater aquatic invertebrates represent one of the most successful groups of organisms. At the same time, the secondary hydrographic system of a river catchment acts as a preferential pathway for the dispersion of Non-Indigenous Species (NIS) to nearby ecosystems. The present study investigates the macrozoobenthos assemblage inhabiting 13 representative semi-natural streams of the secondary hydrographic system of the southern course of the River Ticino (Lombardy, Northern Italy). The level of biocontamination of the habitats under study was assessed by the Site-specific BioContamination Index (SBCI), which was paired with a preliminary screening of the NIS that may cause ecological and economic impacts at the sites under study using the recently-developed Aquatic Species Invasiveness Screening Kit (AS-ISK) tool. The SBCI classified one stream as 'high class', one as 'good class', two as 'moderate class', seven as 'poor class', and the remaining two as 'bad class'. Six macrozoobenthic NIS were identified, namely the amphipod Gammarus roeselii, the gastropods Physella acuta, Potamopyrgus antipodarum and Pseudosuccinea columella, the bivalve Corbicula fluminea and the limpet Ferrissia fragilis . Based on the AS-ISK outcomes, the most potentially invasive species were C. fluminea followed by P. columella, both of which were categorised as 'high risk'. Also, the potential invasiveness of the above species increased after accounting for climate change predictions, as did that for all other species assessed, hence regardless of their corresponding risk level. By combining the results of the SBCI index with those from AS-ISK, a first step is provided towards the identification and refinement of potential management strategies aimed to reduce the impacts of NIS in the RAA, whilst accounting for predicted effects of climate change.